Pengaruh Pengaruh Motivasi Ekstrinsik, Gaya Kepemimpinan, Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Studi Pada Toko Pamella 6 Supermarket Yogyakarta - Anggoro Wisnu Aji; Jajuk Herawati (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
Thisl study aims to determine the effect of extrinsic motivation, leadership style, and work environment on employee job satisfaction at Pamella Enam Supermarket Yogyakarta. This type of research is quantitative. research variables are extrinsic motivation (X1), leadership style (X2), work environment (X3) and job satisfaction (Y). The population in this study were all employees of Pamella Six Supermarket, totaling 60 people and all of them were used as samples. The sampling technique in this study used a saturated sampling technique. The method of data collection in the study used a questionnaire. Data analysis techniques used in this research include reliability test, validity test, multiple linear regression test, classical assumption test through T test, F test, and coefficient of determination. Based on the results of the study, there is a significant positive effect between extrinsic motivation and job satisfaction and leadership style with job satisfaction. However, the work environment has no significant effect on job satisfaction. In this study, extrinsic motivation (X1) has a positive and significant effect on job satisfaction. Leadership style (X2) has a positive and significant effect on job satisfaction. And the work environment (X3) has no significant effect on job satisfaction.